Effect of antibiotic treatment in canine and feline urinary tract infections: A systematic review. Issue 3 (March 2015) - Jessen, L.R.; Sørensen, T.M.; Bjornvad, C.R.; Nielsen, S. Saxmose; Guardabassi, L.
Highlights This study assessed evidence for efficacy of antibiotic treatment in canine and feline urinary tract infections (UTIs). Of 14 peer-reviewed prospective and controlled studies identified, five were randomised controlled clinical trials. There is little evidence concerning antibiotic treatment of UTI in dogs and cats. No clinical studies examined the effect of duration of the same drug. Short duration treatment with trimethoprim-sulfonamide or enrofloxacin was supported by fair evidence, as these treatment strategies were non inferior to medium duration therapy with beta lactams in dogs with uncomplicated cystitis.